2003
DOI: 10.1016/s0168-6445(03)00042-1
|View full text |Cite
|
Sign up to set email alerts
|

Nickel uptake and utilization by microorganisms

Abstract: Nickel is an essential nutrient for selected microorganisms where it participates in a variety of cellular processes. Many microbes are capable of sensing cellular nickel ion concentrations and taking up this nutrient via nickel-specific permeases or ATP-binding cassette-type transport systems. The metal ion is specifically incorporated into nickel-dependent enzymes, often via complex assembly processes requiring accessory proteins and additional non-protein components, in some cases accompanied by nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
410
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(422 citation statements)
references
References 212 publications
(454 reference statements)
7
410
0
5
Order By: Relevance
“…Urea hydrolysis generates NH 3 (Mulrooney & Hausinger, 2003), which may be lost by volatilization. It seems that NH 3 loss contributed to decrease the NH 4 + concentration in the Ur-treated soil, lowering the competition with Ni 2+ for soil adsorption sites and allowing greater Ni 2+ adsorption.…”
Section: Ni In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Urea hydrolysis generates NH 3 (Mulrooney & Hausinger, 2003), which may be lost by volatilization. It seems that NH 3 loss contributed to decrease the NH 4 + concentration in the Ur-treated soil, lowering the competition with Ni 2+ for soil adsorption sites and allowing greater Ni 2+ adsorption.…”
Section: Ni In Soilmentioning
confidence: 99%
“…The urea absorbed by a plant has to be broken down to CO 2 and NH 3 for N assimilation and to prevent urea accumulation in the plant (Marschner, 2008). The Ni-metalloenzyme urease catalyzes the initial step of the urea hydrolysis to CO 2 and NH 3 (Mulrooney & Hausinger, 2003). Therefore, higher urease activity mediated by Ni (Eskew et al, 1984;Brown et al, 1987;Marschner, 2008) helps to prevent urea accumulation in the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel is the most abundant heavy metal contaminants of the environment due to its release during mining and smelting practices (Prasad and Strazalka, 2000). Nickel is required as an essential co-factor in several bacterial enzymes, which carry out metabolic functions (Mulrooney and Hausinger, 2003), but it disrupts processes when it is present in excess (Babich and Stotzky, 1983). Lead is a hazardous waste and is highly toxic to humans, plants and animals (Low et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with our observation that the presence of citrate and malate did not affect the induction of hydrogenase activity in R. leguminosarum cultured cells (our unpublished results). Efficiency of the NikABCDE-dependent Ni transport in E. coli cells increases when Ni is complexed with (L-His) 2 . 18 Consistently, the crystal structure of the periplasmic nickel-binding protein NikA of E. coli in complex with Ni-(L-His) 2 has been subsequently described.…”
Section: Kinetics Of Nickel Transportmentioning
confidence: 99%
“…In the case of the Nik system, crystallographic and spectroscopic data indicate that Ni(II) is bound to NikA as a complex with a small organic molecule, modeled as a butane tricarboxylate, 17 although the biological relevance of this complex could not be demonstrated. A recent study has shown that NikA binds a (L-His) 2 Ni complex, and that Ni(II) and L-His are likely co-transported through the E. coli NikABCDE system. 18 The presence of a similar complex has been demonstrated for the periplasmic binding protein CeuE in H. pylori.…”
Section: Introductionmentioning
confidence: 99%